The Grammartical Error in Speaking English of Student - Dini Mutia Havid; Tarigan, Iren Adina Rahmadani; Harahap, Nury Ana; Putri Nur Aisyah (Philosophiamundi, 2024)
In this era, Grammatical accuracy is a crucial component of effective communication, yet it can be challenging for University Students to speak English. This article aims prevalence of grammatical errors in speaking English and the factors that contribute to them. It also discusses various approaches for identifying and correcting these errors to foster learning and improve spoken language proficiency. The method used is library research with a qualitative approach with the collection of source data from gathering data through classroom observations and semi-structured interviews with learners and instructors. The findings aim to contribute to a deeper understanding of how to find grammatical errors in speaking English, promoting learner speaking skills and fostering the development of Learners.